Sequence-Defined Glycopolymer Segments Presenting Mannose: Synthesis and Lectin Binding Affinity - Ponader, Daniela; Wojcik, Felix; Beceren-Braun, Figen; Dernedde, Jens; Hartmann, Laura (Biomacromolecules, 2012)
We present for the first time the synthesis of sequence-defined monodisperse glycopolymer segments via solid-phase polymer synthesis. Functional building blocks displaying alkyne moieties and hydrophilic ethylenedioxy units were assembled stepwise on solid phase. The resulting polymer segments were conjugated with mannose sugars via 1,3-dipolar cycloaddition. The obtained mono-, di-, and trivalent mannose structures were then subject to Con A lectin binding. Surface plasmon resonance studies showed a nonlinear increase in binding regarding the number and spacing of sugar ligands. The results of Con A lectin binding assays indicate that the chemical composition of the polymeric scaffold strongly contributes to the binding activities as well as the spacing between the ligands and the number of presented mannose units. Our approach now allows for the synthesis of highly defined glycooligomers and glycopolymers with a diversity of properties to investigate systematically multivalent effects of polymeric ligands.